A microwave method for plastic embedding of nervous tissue for light and electron microscopy - Calkins, Evan (Heliyon, 2019)
BACKGROUND: Fast, effective, and rapid processing of central nervous system (CNS) tissue with good preservation of myelin, especially in tissue from diseased mice, is important to many laboratories studying neurosciences. NEW METHOD: In this paper, we describe a new method to process and embed CNS tissue from mice. Spinal cords and optic nerves from naive C57BL/6 mice were used to standardize the microwave protocol following perfusion with fixative. The CNS tissue was processed and embedded using the microwave embedding protocol. RESULTS: We observed that the tissue is well preserved and good quality light and electron microscope images were obtained after using the microwave embedding protocol. COMPARISON WITH EXISTING METHODS: Traditional way of embedding CNS tissue in resin is challenging and time consuming. The microwave technology offers an efficient way to quickly embed CNS tissue while preserving morphology and retaining the integrity of the myelin. CONCLUSIONS: This new method is fast, reliable and an effective way to embed CNS tissue in resin.